Development of drift-flux correlations for vertical forward bubble column-type gas-liquid lead-bismuth two-phase flow - Wang, Di; Lu, Xianghui; Qiu, Suizheng; Liang, Ren; Lin, Zhikang; Ouyang, Yong (Frontiers in Energy Research, 2022)
Bubble column represents an extreme case of gas-liquid two-phase flow that bubble flow where net liquid velocity is zero and the gas simply bubbles up through the liquid. The bubble column-type gas-liquid metal two-phase flow always appears in accident scenario of pool-type lead-bismuth eutectic cooled fast breeder reactors. To accurately predict the void fraction for accident evaluation and design of reactor system, 9 exist drift-flux type constitutive correlations are evaluated with nitrogen-liquid heavy metal two-phase flow test. Few correlations give relatively good prediction and the basic assumption in distribution parameter calculation is not applicable for bubble column. To solve this problem, analysis based on Clark’s theoretical model is carried out. Result shows that distribution parameter is assuming very high values at low Re number. Besides, with Froude number increase, distribution parameter tends to decrease. At lower void factions, distribution parameter is also assumed to be high values. It indicates that the pipe size, flow rate and void fraction can all influence distribution parameter. Considering the quantitative laws of above influence factors obtained by theoretical analysis and fitting the data of Ariyoshi’s test, a new correlation for bubble column-type gas-LBE two-phase flow is developed and evaluated. Statistical analysis result shows that new correlation gives the best prediction for gas-LBE two-phase flow in the void fraction range of 0.018 0.313.